Ecology and behaviour of the franciscana (Pontoporia blainvillei) in Bahia Anegada, Argentina - Bordino, Pablo; Thompson, Gustavo; Iniguez, Miguel (J. Cetacean Res. Manage., 1999)
From January 1993 to July 1997, franciscana sightings were recorded from shore-based stations and vessels at Bahfa Anegada, Argentina. In total, 321 hours were spent in direct observation of dolphins following the Ad libitum and Focal sampling methods. The present study provides information on the ecology and behaviour of the franciscana in the study area. A total of 25lsightings were made and the number of sightings per unit effort (SPUE) was significantly greater during spring (p = 0.001). Dolphins were recorded at a mean distance from shore of 3.2km (0.4km-10.7km), although they were found at a significantly greater mean distance from shore during winter (p = 0.005). More sightings were recorded during flood tide than during ebb tide (p = 0.016). A higher SPUE was also recorded from a sailboat than from a motor boat (p = 0.005). Group size was small, ranging from 1 to 6 individuals. Calves were recorded during spring and summer and only one calf was observed per group. The behaviour showed a seasonal pattern with co-operative feeding and travelling activities increasing during winter. Tide and depth also influenced behaviour. Co-operative feeding increased during flood tide, while travelling decreased. The behavioural ecology of the franciscana appears similar to that of other coastal and river dolphins. This study represents the first attempts to understand the behaviour of the franciscana in its natural habitat.